Kemiskinan Rumah Tangga Petani di Daerah Transmigrasi: Studi Kasus Desa Waihatu Kecamatan Kairatu Kabupaten Seram Bagian Barat - Gultom, Eka N; Girsang, Wardis; Parera, Weldemina B (Universitas Pattimura, 2025)
This research aims to find out how big the level of poverty and inequality is in Waihatu Village, Kairatu District, West Seram Regency. The number of respondents was 50 (12%), who were determined simply randomly from 430 farming households. Primary data was obtained through observation and interviews using questionnaires, and secondary data was obtained from references to documents and previous research results. The research results show that food expenditure is greater than non-food expenditure. There were 7 (people) poor respondents, and the gap in Waihatu was low because the bottom 40% received 18% (34%) of total expenditure.